2003
DOI: 10.1172/jci200316956
|View full text |Cite
|
Sign up to set email alerts
|

Collecting duct–specific gene inactivation of αENaC in the mouse kidney does not impair sodium and potassium balance

Abstract: Aldosterone controls the final sodium reabsorption and potassium secretion in the kidney by regulating the activity of the epithelial sodium channel (ENaC) in the aldosterone-sensitive distal nephron (ASDN). ASDN consists of the last portion of the distal convoluted tubule (late DCT), the connecting tubule (CNT), and the collecting duct (CD) (i.e., the cortical CD [CCD] and the medullary CD [MCD]). It has been proposed that the control of sodium transport in the CCD is essential for achieving sodium and potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 39 publications
7
106
2
Order By: Relevance
“…The previously described CD-specific KO mice (Scnn1a lox/lox /HoxB7::Cre) were used as positive (and negative) control. 10 In the CNT and the CCD of all control groups, a band at approximately 95 kD corresponding to full-length ␣ENaC protein was observed ( Figure 1A, lanes 1 and 2, and B, lanes 1 and 2 and lanes 5 and 6). This band was absent in the CCD of the CD-specific KO mice ( Figure 1A, lane 4) 10 and in the CCD of the CNT/CD-specific KO mice (Figure 1B, lanes 4 and 8).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The previously described CD-specific KO mice (Scnn1a lox/lox /HoxB7::Cre) were used as positive (and negative) control. 10 In the CNT and the CCD of all control groups, a band at approximately 95 kD corresponding to full-length ␣ENaC protein was observed ( Figure 1A, lanes 1 and 2, and B, lanes 1 and 2 and lanes 5 and 6). This band was absent in the CCD of the CD-specific KO mice ( Figure 1A, lane 4) 10 and in the CCD of the CNT/CD-specific KO mice (Figure 1B, lanes 4 and 8).…”
Section: Resultsmentioning
confidence: 91%
“…10 In the CNT and the CCD of all control groups, a band at approximately 95 kD corresponding to full-length ␣ENaC protein was observed ( Figure 1A, lanes 1 and 2, and B, lanes 1 and 2 and lanes 5 and 6). This band was absent in the CCD of the CD-specific KO mice ( Figure 1A, lane 4) 10 and in the CCD of the CNT/CD-specific KO mice (Figure 1B, lanes 4 and 8). We observed a faint band corresponding to full-length ␣ENaC protein in the CNT of the CNT/CD-specific KO mice ( Figure 1B, lanes 3 and 7), suggesting that the inactivation of ␣ENaC in the CNT was not complete.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…At the time of the second nephrectomy and adrenalectomy, an osmotic minipump (ALZET model 2004; DURECT Corporation) containing aldosterone (A12930; Pfaltz & Bauer) and dexamethasone (D-1756; Sigma-Aldrich) was placed in a subcutaneous pouch. The doses of aldosterone (1 μg/day) and dexamethasone (1.2 μg/100 g body wt/d) were chosen to provide near-physiological replacement based on published studies (43,44). The aldosterone and dexamethasone were dissolved in polyethylene glycol 400 (Sigma-Aldrich) (45) and further diluted in normal saline.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we used conditional gene targeting of ENaC to genetically dissect the aldosterone-induced ENaC-mediated sodium reabsorption along the nephron. When a floxed allele for the αENaC subunit (Scnn1a lox/lox mice) [38] was crossed with the HoxB7::Cre line this resulted in a complete abolishment of ENaC function in the cortical collecting duct (CCD), but not in the early segments of the aldosterone-sensitive distal nephron (ASDN), the late distal convoluted tubule (DCT) and connecting tubule (CNT) [85]. Surprisingly, we found that ENaC expression in the CCD is not a prerequisite for normal sodium and potassium balance.…”
Section: Mouse Models For Kidney Diseasesmentioning
confidence: 99%